Internal Limiting Membrane Peeling versus Nonpeeling to Prevent Epiretinal Membrane Formation following Vitrectomy for Posterior Segment Open-Globe Injury - Wen-Long Wei; Zhong Lin; Ming-Na Xu; Ke-Mi Feng; Zhen-Quan Zhao (Journal of Ophthalmology)
Purpose. Approximately 30% of patients with an open-globe injury (OGI) develop a secondary epiretinal membrane (ERM). This study was performed to assess whether internal limiting membrane (ILM) peeling in the treatment of posterior segment OGI prevents ERM formation. Methods. The medical records of 33 patients who underwent vitrectomy for posterior segment OGI from 2016 to 2019 were retrospectively analyzed. Of these patients, 17 underwent ILM peeling during the vitrectomy and 16 did not. The patients’ demographic and surgical data were collected. The associations of ILM peeling with the preoperative findings of posterior segment OGI and development of a postoperative ERM were analyzed. Student’s t-test was used to evaluate differences in continuous variables, and the chi-squared test or Fisher’s exact test was used for categorical variables. Time-to-event curves were calculated from postestimation Cox proportional hazards models. Results. An ERM developed in three eyes (17.6%) in the ILM peeling group and in eight eyes (50.0%) in the nonpeeling group (p<0.05). There was no statistically significant difference between the groups in visual acuity at baseline (1.68 vs. 1.58 logMAR, p=0.68) or at final follow-up (0.72 vs. 0.78 logMAR, p=0.66). Median visual acuity significantly improved in both groups (p<0.001). In the multivariable models, ILM peeling (odds ratio, 0.19; 95% confidence interval, 0.04–0.91; p=0.04) and worse preoperative vision (odds ratio, 0.29; 95% confidence interval, 0.10–0.80; p=0.02) were associated with lower likelihood of ERM formation. Conclusion. Preventative treatment with ILM peeling contributed to decreased development of an ERM in patients with OGI involving areas near the fovea.